Optical and thermal properties of transparent infrared blocking antimony doped tin oxide thin films - Abendroth, Thomas; Schumm, Benjamin; Alajlan, Saleh A.; Almogbel, Ahmed M.; Maeder, Gerrit; Haertel, Paul; Althues, Holger; Kaskel, Stefan (Thin Solid Films, 2017)
Antimony doped tin oxide thin films show outstanding optical, electrical and thermal properties. Here, we report the preparation of 100–500 nm thick undoped and antimony doped tin oxide films on glass substrates by aerosol-assisted chemical vapor deposition in order to evaluate the films for solar control glazing applications. The structural, electrical and optical properties are studied for variable antimony doping levels (0 at%–22.5 at% in the film) and deposition temperatures (300–600 °C). The influence of antimony doping levels on absorption and reflection is evaluated with respect to tune optical properties in the visible and near infrared range. Compared to commercially available glazing (e.g. from Saudi-Arabian glass companies) an improved solar blocking behavior is observed for nanostructured ATO thin films.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Aerosol assisted chemical vapor deposition; Antimony-doped tin oxide; Electrical properties; Optical properties; Solar control glazing; Structural properties